NON-METALLIC IMPURITIES AND FORMING OF THE STRUCTURE OF THE MODIFIED HIGH-MANGANESE STEEL - A. I. Garost (Литьë и металлургия)
The composition and morphology of chemical associations (non-metallic impurities and other ‘‘secondary” phases) at modification of high-manganese steel by nitrogen and nitrideforming elements (vanadium) are investigated. The optimal compositions of steel for production of castings are offered. The technology of the steel wear-resistance modification by vanadium of waste of industrial enterprises is worked out.